A Comparative Study Done by Male and Female Hate Speech Comments on Nikita Mirzani’s Instagram - Siahaan, Restu Berka; Sihite, Jubil Ezer; Pasaribu, Donna Ria (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aimed to find out the types of impoliteness strategy of hate speech and the most dominant type of impoliteness strategy of hate speech used by Male and Female Hate Speech Comments on Nikita Mirzani’s Instagram. This study is a qualitative research with a descriptive design. In analyzing the data, the writer selected comments that show impoliteness strategies of hate speech on Nikita Mirzani posts on March, 4th 2023, and analyzed the data based on Culpeper (1996) theory. In this study, the writer found there are 100 the data that divided into two categories: 50 comments made by male netizens and 50 comments by female netizens. In this study there are four types of impoliteness strategies found in comments namely, there are 16 (32%) data of bald on record impoliteness for male and 7 (14%) data for female, 13 (26%) data of positive impoliteness for male and 16 (32%) data for female, 12 (24%) data of negative impoliteness for male and 14 (28%) data for female, and the last one is 9 (18%) data of sarcasm impoliteness for male and 13 (26%) data for female in comments Nikita Mirzani instagram account. Based on the results, the most dominant type of strategy impoliteness of hate speech used by male is bald on record impoliteness with 16 (32%) and for female is positive impoliteness with 16 (32%) data comment. The findings show that male and female netizens are different in expressing hate speech against Nikita Mirzani. Male netizens tend to be clearer, harsher, and straightforward than female in expressing their hatred.